The Role of Contrastive And Error Analysis In Second Language Acquisition: A Theoretical And Applied Study/ دور التحليل التقابلي وتحليل الأخطاء في اكتساب اللغة الثانية: دراسة تأصيلية وتطبيقية - Alsaedi, Maher Dakhilallah (Ijaz Arabi Journal of Arabic Learning, 2025)
This study aims to explore the complementary role of contrastive analysis (CA) and error analysis (EA) in facilitating second language acquisition (SLA) and enhancing learners’ linguistic competence. The research employed a descriptive-analytical approach to examine key theoretical concepts and models, particularly hierarchical models of language learning difficulties such as Prator’s and Stockwell’s frameworks, alongside a review of applied studies in language education. The findings indicate that contrastive analysis provides a crucial predictive framework that helps identify potential areas of difficulty based on structural differences between the learners’ first language (L1) and the target language (L2), thus enabling the design of more responsive instructional content. Meanwhile, error analysis is a diagnostic tool that reveals learners’ linguistic performance and sheds light on the transitional rules they construct during acquisition. The study also showed that hierarchical models enhance the precision of contrastive analysis by categorising linguistic differences according to varying levels of complexity and difficulty, which supports preempting errors and guiding instruction more effectively. The study concludes by underscoring the importance of integrating contrastive and error analyses in curriculum development and teaching strategies, training teachers to analyse and classify errors and devise remedial plans that respect learners’ linguistic and cultural backgrounds, thereby transforming errors from obstacles into learning opportunities. It recommends developing instructional units based on well-studied maps of linguistic difficulties, which improve SLA quality and foster learners’ awareness, confidence, and linguistic competence.